(untitled) (Contemporary Journal of Social Science Review, 2025)
The present study aims to identify the factors responsible for the language shift from Punjabi to Urdu and English. The research focuses on social, political, economic, demographic, technological, and attitudinal factors that compel speakers’ language shift from Punjabi to Urdu and English. Moreover, it also aims to investigate whether this shift is positive or negative and highlight the young generation’s attitudes towards the Punjabi language. The study instrument was a five-point Likert scale questionnaire adopted from two relevant studies (Gillani et al., 2014 & Nazir et al., 2013), primarily designed by Gardner’s Attitudinal Motivation Test Battery (ATMB), containing 24 statements and one open-ended question. The research population was undergraduates and postgraduates of the University of Sargodha (UOS). A random sample of 88 participants was taken, and data were analyzed through IBM SPSS software. Domain theory by Joshua A. Fishman (1972) and Ethnolinguistics Vitality Theory (EVT) by Giles, Bourhis, and Taylor (1977) are applied as a theoretical and analytical framework to determine the role of sociocultural features that affect the strength of language choices in a multilingual context, and help to find the language shift and language preservation. Findings show that low prestige, linguistic shame, lack of technological advancements, and lack of governmental and institutional support are reasons behind the Punjabi language shift, and respondents saw the shift as positive, having no emotional attachment. The research provides empirical evidence of the Punjabi shift and helps to preserve Pakistan’s cultural and linguistic diversity of the indigenous languages.